PENGARUH KEMAMPUAN KERJA DAN PERILAKU KARYAWAN TERHADAP KINERJA KARYAWAN PT.BINTANG NIAGA SINERGI (ID EXPRESS) PALEMBANG - Muhammad Yusuf; Wiwin Agustian (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This research aims to examine the influence of work abilities and employee behavior on the performance of PT. Bintang Niaga Sinergi (Id Express) employees. The method used is quantitative, the object of this research is the employees of PT. Bintang Niaga Sinergi (Id Express). The respondents in this research were 38 employees of PT. Bintang Niaga Sinergi (Id Express), collecting data using a questionnaire. Sampling in this study used a saturated sampling technique, namely sampling carried out as a whole from the total population. The data analysis technique was carried out using SPSS version 20. The results of this research show that first, work ability has a significant effect on employee performance (H1 is accepted), second, employee behavior has a significant effect on employee performance (H2 is accepted). It is hoped that this research can add information and reading references, thereby increasing knowledge about employee work abilities and behavior.